THE ROLE OF REMORSE IN SENTENCING - Pieter du Toit (Obiter, 2021)
It has become an established feature of the South African sentencing practice to consider the level of remorse displayed by the accused. Genuine contrition or remorse is generally regarded as a mitigating factor whilst the absence thereof is considered to be an aggravating factor. Our courts link the presence of remorse with the prospect of the rehabilitation of the offender. In S v Seegers (1970 (2) SA 506 (A) 512G–H) Rumpff JA held that remorse, as an indication that the offence will not be committed again, is an important consideration, in suitable cases, when the deterrent effect of a sentence on the accused is considered. This note considers the meaning of “remorse” in the eyes of our courts, the approach of South African courts (in particular the Supreme Court of Appeal) to the role of remorse in sentencing, as well as the question whether the presence or absence of remorse can truly be determined by a court.